1988
DOI: 10.1021/bi00424a012
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization and reconstitution of the D-1 dopamine receptor: potentiation of the agonist high-affinity state of the receptor

Abstract: The D-1 dopamine receptor was extracted from rat striatal membranes with sodium cholate and NaCl in the presence of a specific agonist and phospholipids. The soluble receptor then was reconstituted into phospholipid vesicles by further addition of phospholipids prior to detergent removal. Of the total membrane receptors, up to 48% were extracted and 36% were reconstituted into phospholipid vesicles. Yields were greatly reduced if the agonist was omitted or replaced with an antagonist. The solubilized and recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 29 publications
7
42
0
Order By: Relevance
“…2A); from the data, an association rate constant (k+,) of 3.05 X nM-' min-' was calculated ( Fig. 2A, inset) as described by Sidhu (1988). Bound [3H]NPY was displaced by unlabeled NPY in a time-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2A); from the data, an association rate constant (k+,) of 3.05 X nM-' min-' was calculated ( Fig. 2A, inset) as described by Sidhu (1988). Bound [3H]NPY was displaced by unlabeled NPY in a time-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…We had earlier demonstrated that, on solubilization and reconstitution of brain D-1 dopamine receptors into phospholipid vesicles, the agonist high-affinity sites were potentiated and comprised 40-50% ofthe total receptor population (21,22). These potentiated sites were due to increased coupling of receptor to G protein and were abolished by guanine nucleotide analogues.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased ability ofDA-1 agonists to stimulate AC activity was not due to a defective AC enzyme per se but rather to a defective DA-l receptor-AC coupling mechanism (19). To investigate the mechanism for the defective DA-l dopamine receptor in the SHR and to develop a cell-free system (21,22) MO), whereas SM-2 Bio-Beads were from Bio-Rad Laboratories (Richmond, CA). Dulbecco's PBS (DPBS) was purchased from Gibco Laboratories (Grand Island, NY).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations